The Influence of pH and Temperature on Development of Pathogens of Dieback Disease on The Nutmeg Tree In Aceh Selatan In Vitro - Susanna; Meity S. Sinaga (MUSURGIA, 2019)
The ability of microorganisms to grow and stay alive is an important thing to know. Factors that play a role in the development of life of the pathogen can be used as a bases to inhibit the development or decrease inoculums population in the field. The objectives of this study were to determine the effect of pH and temperature in vitro. Four of pathogenic fungi (Lasiodiplodia theobromae, Graphium euwalaceae, Fusarium solani, dan Rigidoporus microporus) were tested for growth at pH media include 3, 4, 5, and 6 while the effect of temperature include 16, 22, 28, and 34 oC. The results showed that L. theobromae had a wide range of pH and temperature compared to three other fungi. Optimum pH medium for mycelia growth is 4 to 6 and the optimum temperature is 28 oC. The lower the pH causes the mycelial growth to be inhibited, as well as the temperature. When the temperature is lowered or increased, the mycelial growth is disturbed.